Implementation of The Good Documentation Practice In Manufacturing Area - Sumarna, Alfonsa Dian; Sihite, Emy Angely Christina Prawasta Br (ABEC Indonesia, 2023)
This study discusses the problems faced at the company about good documentation practice error, this is due to the absence of work instructions to double-check the documentation carried out. This study aims to reduce good documentation practice errors in plasma production areas by adding work instructions, namely double-checking each documentation. The methods used in this study are observational research methods, documentation, interviews, and Garret Rank methods. The conclusion of the study is that at company already has SOPs on good documentation practice and has followed them in accordance with the good documentation practice standards that have been written.